Simulation experiment of fluid-feldspar sandstone interactions and their implications for tight oil and gas exploration of the Yanchang Formation, Ordos Basin, China. (August 2022) - Ma, Zhongliang; Tan, Jingqiang; Zheng, Lunju; Ni, Chunhua; Hu, Ruining; Ma, Jianfei
Abstract: Tight oil and gas reservoirs are generally formed in structurally stable and broad buffer zones, with high-quality source rocks developed in large areas and sand bodies in extensive contact with source rocks. Fluids generated from source rock during the thermal maturation are bound to dissolve or precipitate in the adjacent reservoir, which directly restricts the pore development of the reservoir and the direction of oil and gas exploration. To reveal the effect of the total component fluids from source rock on reservoir transformation during hydrocarbon evolution, taking the Yanchang Formation of the Ordos Basin as an example, a fluid-feldspar sandstone interaction simulation experiment of different geological evolution stages under a closed environment was carried out. The results show that the fluids that formed in the hydrocarbon evolution process contain organic acids, and consist mainly of acetic acid. At the peak period of oil generation (VRo = 0.96%), the fluids are the most acidic, the acetic acid yield is the highest, and the average molar ratio is 56.11%. Under closed conditions, after the fluid-feldspar sandstone interaction, the feldspar minerals are altered and clay minerals are generated in situ, which results in a tight reservoir. The feldspar mineral content decreased from 26.1% to 20.8%–22.3%, clay mineral content increased from 11% to 14.30%–14.37%, porosity decreased 5.18%–28.79%, and permeability decreased 4%–34.16%. In addition, a semi-quantitative evaluation method of feldspar dissolution and porosity was established, which was used to evaluate the effect of fluids on feldspar sandstone reservoirs during hydrocarbon evolution. The local semiclosed or open diagenetic system and acid fluid transport and accumulation area beneficial to the formation of the "sweet spot" of tight oil and gas. However, the gentle tectonic setting and extensive contact of sand and mudstone lead to the retention effect of diagenetic fluid in the Yanchang Formation of the Ordos Basin. Oil and gas exploration should be mainly directed to finding sedimentary sand facies bodies favorable for the formation and preservation of primary pores. Highlights: A source-reservoir cooperative evolution simulation device was used to evaluate the "sweet spot" of tight oil and gas. Acetic acid is the main fluid formed during the evolution of source rocks. Closed diagenetic environment, feldspar minerals dissolve and clay minerals form in situ, resulting in reservoir's tight. Semiclosed or open diagenetic system and acid fluid transport area beneficial to the "sweet spot" of tight oil and gas.